Wall Paintings 1 + 9 / 9 + 1. - Kaiser, Franz W. (Mechelen : bkSM (beeldende kunst Strombeek-Mechelen), 2008)
Binst, Luc ; Förg, Gunther ; Clinckx, Christine ; Arocha, Carla ; Schraenen, Stéphane ; Geyskens, Vincent ; Van Imschoot, Jan ; Ioannou, Athina ; Noiret-Thomé, Xavier ; Raat, Thomas ; van der Stokker, Lily ; Suermondt, Robert ; Tuerlinckx, Joëlle
Wall Paintings 1+9 / 9+1, cultuurcentrum, Strombeek Grimbergen, 2008-10-12. 2008-12-14
boek